PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA ANGGOTA PADA SPKT (SENTRA PELAYANAN TERPADU) KORPOLAIRUD BAHARKAM POLRI - Akka Latifah Yusdinar; Yari Harjo (Sekolah Tinggi Manajemen IMMI Jakarta, 2019)
The method of research conducted by surveying 100 respondents from a population of 100 Polpulasi with a structured method using questionnaire instruments using the Likert measurement scale, analysis techniques and using classical tests, multiple regression, and the results of research simultaneously and in parallel shows the influence of motivation and discipline on employee performance. There is a significant effect of Motivation on Member Performance in the SPKT Section of KORPS POLAIRUD Baharkam Polri, this is obtained by t table: tcount 1.884 ttable 1.658, and R² of 0.364 (36.40%). There is a significant influence of discipline on the Performance of Members in the SPKT Korpolairud Section Baharkam Baharkam Polri, this is obtained by t table: tcount 7.333 t table 1.658, and R² of 0.364 (36.40%).From the results of statistical calculations can be explained. R value of 0.603 and Squere R value (r determinant) of 0.364 gives the meaning that the motivation variable and discipline variable on employee performance has an effect of 36.40% on the performance variable. Meanwhile, the remaining 63.60 ^% is influenced by other factors not discussed in this study.